ON THE IMPLEMENTATION OF COORDINATED SCIENTIFICTECHNICAL PROGRAMS IN VETERINARY PARASITOLOGY - A. V. Uspensky; E. I. Malakhova; V. Ya. Shubaderov (Российский паразитологический журнал, 2016)
Fundamental and applied studies on the regularities of formation and functioning of parasitic systems and their components in natural and agricultural biocenoses of different ecological and climatic zones in Russian Federation and some CIS countries were carried out.  Monitoring and forecast of epizootic situation on parasitic diseases in farm animals and wildlife was conducted. Methods for prevention and fight against parasitoses were elaborated. Search for the next generation of diagnostic tools and complex remedies for protection of animals was conducted.